2010
DOI: 10.1007/s11940-010-0080-y
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drugs and Markers of Vascular Risk

Abstract: The most-used treatments for epilepsy worldwide are older-generation drugs such as phenytoin, carbamazepine, phenobarbital, and valproic acid, which have prominent enzymatic effects. Our sense of comfort with these treatments is starting to fade, however, as more and more potential long-term consequences of these drugs come to light. Epidemiologic studies demonstrate that ischemic disease of the heart and brain is more common among patients with epilepsy. Enzyme-inducing drugs are associated with elevations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 53 publications
(58 reference statements)
5
76
0
Order By: Relevance
“…This effect may largely be explained by these agents upregulating mitochondrial biogenesis. [60][61] [62] The issue of drug resistance by alterations in GABA-A receptor and increased MDR especially in temporal lobe epilepsy may also be significantly addressed by this sequential drug combination therapy. [62][63] For example, artesunate and the PPIs may inhibit P-glycoprotein (P-gp) or multi-drug resistance protein-I.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may largely be explained by these agents upregulating mitochondrial biogenesis. [60][61] [62] The issue of drug resistance by alterations in GABA-A receptor and increased MDR especially in temporal lobe epilepsy may also be significantly addressed by this sequential drug combination therapy. [62][63] For example, artesunate and the PPIs may inhibit P-glycoprotein (P-gp) or multi-drug resistance protein-I.…”
Section: Discussionmentioning
confidence: 99%
“…AEDs are implicated because many AEDs induce CYP450 enzymes that participate in cholesterol synthesis. More than ten cross-sectional studies of adults and children have found elevated total cholesterol in carbamazepine-treated patients relative to controls or valproated-treated patients (30). Likewise, a half-dozen studies of phenobarbital showed elevated cholesterol.…”
Section: Antiepileptic Drugs and Cardiovascular Diseasementioning
confidence: 99%
“…In patients with late-onset seizures treated with antiepileptic drugs, treatment itself might indirectly increase the risk of stroke, possibly playing a synergistic effect with the occult cerebrovascular disease. Enzyme-inducing antiepileptic drugs may actually increase total cholesterol, lipoprotein(a), C-reactive protein, and homocysteine levels [16]. Whether this pharmacological effect on surrogate markers of vascular disease is clinically relevant or not remains to be defined.…”
mentioning
confidence: 99%